Intelligent Evacuation Guidance for Fire Response in Super High-rise Buildings - Lee, Chul-Gyoo; Moon, Sang-Ho; Yu, Young-Jung; Park, Seong-Ho (International Journal of Engineering and Technology, 2019)
Recently, urban structures including buildings are becoming increasingly large and super high-rise making human life more convenient. As the number of super high-rise buildings increases, the risk of fire and other disasters is also increasing. Deaths and injuries would be tremendous than imagined if the evacuation guidance would not be provided promptly and precisely for the occupants in case of a fire in super high-rise buildings. Therefore, rapid rescue should be done for those who are in need of immediate assistance or rescue in the building. In this paper, the proponents propose a method for intelligent evacuation guidance by deriving the optimal evacuation route based on the fire location. To do this, a simulation and modeling method is also being proposed for calculating the optimal evacuation route based on the fire location, the number of residents and evacuation speed information when a fire occurs in super high-rise buildings. For this to happen, the evacuation type that is suitable for building type and resident characteristics must first be extracted through the evacuation simulator. If a fire actually occurs, evacuation proceeds according to the scenario extracted through the simulator. When the evacuation starts, the location information and the evacuator speed information are being collected in real time. Using this information, a modified evacuation route that can shorten the evacuation time would be obtained using the evacuation route change condition formula. Also, the location-based evacuation model informs residents of the optimal evacuation route and provides firefighters with location information of residents. This study models the optimal evacuation method for super high-rise buildings by simulating the evacuation type selection and implementing the evacuation route change condition formula using the location information collected in real time. Finally, the location-based evacuation model consists of the location identification technique required to derive the evacuation route and the optimal evacuation route calculation based on the resident's location information.Â